2017
DOI: 10.3389/fnagi.2017.00073
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transcriptomic Meta-analysis Identifies Dysregulation of Hemoglobin and Iron Metabolism in Parkinson’ Disease

Abstract: Disrupted iron metabolism has been implicated in the pathogenesis of Parkinson’s disease (PD), a progressive neurodegenerative disorder that severely affects movement and coordination, yet the molecular mechanisms underlying this association remain unknown. To this end, we performed a transcriptomic meta-analysis of four blood microarrays in PD. We observed a significant downregulation of genes related to hemoglobin including, hemoglobin delta (HBD), alpha hemoglobin stabilizing protein (ASHP), genes implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 42 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in PD blood transcriptomics 3941 . Therefore, these genes have the potential to serve as blood biomarkers for PD vulnerability.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 42 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in PD blood transcriptomics 3941 . Therefore, these genes have the potential to serve as blood biomarkers for PD vulnerability.…”
Section: Discussionsupporting
confidence: 52%
“…One previous case-control study showed that anemia or low hemoglobin levels may precede the onset of PD 38 . Several studies using blood transcriptomic meta-analysis revealed genes associated with hemoglobin and iron metabolism were downregulated in PD patients compared to controls 3941 . In our study, several hemoglobin genes ( HBD, HBB, HBA1 , HBA2 , and OASL ) were also present in module M47 of which HBD and HBB have been described to be highly interconnected with SNCA 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a significant loss of negative co-expression between SNCA and interferon-gamma genes in the substantia nigra has been demonstrated in PD patients as compared to controls 41 . This loss may result from a downregulation of genes within M47 in the substantia nigra of PD patients, similarly as was observed in blood transcriptomics of PD [38][39][40] . This could be confirmed for ATXN3 in the substantia nigra of PD patients 42 .…”
Section: Discussionmentioning
confidence: 56%
“…One previous case-control study showed that anemia or low hemoglobin levels may precede the onset of PD 37 . Several studies using blood transcriptomic meta-analysis revealed genes associated with hemoglobin and iron metabolism were downregulated in PD patients compared to controls [38][39][40] . In our study, several hemoglobin genes (HBD, HBB, HBA1, HBA2, and OASL) were also present in module M47 of which HBD and HBB have been described to be highly interconnected with SNCA 40 .…”
Section: Discussionmentioning
confidence: 99%